Recent Advances in Therapeutics for the Treatment of Alzheimer’s Disease - Amin Mahmood Thawabteh; Aseel Wasel Ghanem; Sara AbuMadi; Dania Thaher; Weam Jaghama; Donia Karaman; Rafik Karaman (Molecules)
The most prevalent chronic neurodegenerative illness in the world is Alzheimer’s disease (AD). It results in mental symptoms including behavioral abnormalities and cognitive impairment, which have a substantial financial and psychological impact on the relatives of the patients. The review discusses various pathophysiological mechanisms contributing to AD, including amyloid beta, tau protein, inflammation, and other factors, while emphasizing the need for effective disease-modifying therapeutics that alter disease progression rather than merely alleviating symptoms. This review mainly covers medications that are now being studied in clinical trials or recently approved by the FDA that fall under the disease-modifying treatment (DMT) category, which alters the progression of the disease by targeting underlying biological mechanisms rather than merely alleviating symptoms. DMTs focus on improving patient outcomes by slowing cognitive decline, enhancing neuroprotection, and supporting neurogenesis. Additionally, the review covers amyloid-targeting therapies, tau-targeting therapies, neuroprotective therapies, and others. This evaluation specifically looked at studies on FDA-approved novel DMTs in Phase II or III development that were carried out between 2021 and 2024. A thorough review of the US government database identified clinical trials of biologics and small molecule drugs for 14 agents in Phase I, 34 in Phase II, and 11 in Phase III that might be completed by 2028.